Employment effects of environmental policies - Mohommad, Adil (International Monetary Fund, 2021)
The employment impact of environmental policies is an important question for policy makers. We examine the effect of increasing the stringency of environmental policy across a broad set of policies on firms' labor demand, in a novel identification approach using Worldscope data from 31 countries on firm-level CO2 emissions. Drawing on evidence from as many as 5300 firms over 15 years and the OECD environmental policy stringency (EPS) index, it finds that high emission-intensity firms reduce labor demand upon impact as EPS is tightened, whereas low emission-intensity firms increase labor demand, indicating a reallocation of employment. Moreover, tightening EPS during economic contractions appears to have a positive effect on employment, other things equal. Quantifications exercises show modest positive net changes in employment for market-based policies, and modest negative net changes for non-market policies (mainly emission quantity regulations) and for the combined aggregate EPS. Within market-based policies, the percent decline in employment in high-emission firms (correspondingly the increase in low-emission firms) for a unit change in a policy index is smallest (largest) for trading schemes ('green' certificates, and 'white' certificates)-although stringency is not comparable across indices. Finally, the employment effects of EPS are not persistent
10.5089/9781513573618.001
Keywords: Graue Literatur; Environmental regulation; Employment; Foreign Exchange; Informal Economy; Underground Econom; Unemployment; Natural Resources; International Economics; Environmental Policy; Macroeconomics; Environmental Conservation and Protection; Wages; Intergenerational Income Distribution; Aggregate Human Capital; Aggregate Labor Productivity; Environmental Economics: Government Policy; Climate; Natural Disasters and Their Management; Global Warming; Labor Demand; Nonrenewable Resources and Conservation: General; Economic & financial crises & disasters; Economics of specific sectors; Labour; income economics; Environmental policy & protocols; Climate change; Environmental management; Financial crises; Economic sectors; Economics: General; Labor; Environment; Greenhouse gas emissions; Labor demand; Non-renewable resources; Currency crises; Informal sector; Economics; Employment; Economic theory; Environmental policy; Greenhouse gases; Labor market; Natural resources